Horizontes culturales de la historia del arte : aportes para una acción compartida en Colombia - Salcedo Fidalgo, Diego; Cordero Reiman, Karen, 1957- (Editorial UTADEO, Universidad de Bogotá Jorge Tadeo Lozano, 2018)
"This text arises from a need: the socialization and visibility of the investigative processes carried out during the last decade in the Department of Humanities of the University of Bogotá Jorge Tadeo Lozano. In this context, a constant research has been developed around the discipline of History of Art and its discursive, pedagogical and professionalization possibilities, oroginating within the process the undergraduate course in History of Art and the Masters in Aesthetics and History of Art." (HKB Translation) --Page 16.